THE CONSEQUENCES OF MENTAL INJURY IN SCHOOL STUDENTS - Azgarova Gulsum Alisherovna (Journals Park Publishing, 2023)
This article describes the elimination of mental stress in preschool children, as well as their elimination of negative consequences after psychological trauma.
Keywords: mental stress, family environment, aggression, consequences of mental stress.